QOL-25. IMPACTS OF IMPLEMENTING A PROSPECTIVE TREATMENT AND SURVEILLANCE PROTOCOL FOR THE MANAGEMENT OF NF2-ASSOCIATED VESTIBULAR SCHWANNOMAS ON TUMOR GROWTH, HEARING OUTCOMES, AND QUALITY OF LIFE. (14th November 2022) - Rousseau, Julien; Dahoud, Andrea; Labidi, Moujahed; El Haffaf, Zaki; Florescu, Marie; Saliba, Issam; Gosselin, Marie-Hélène; Lapointe, Sarah
Abstract: Neurofibromatosis type 2 (NF2) is an autosomal dominant neurocutaneous syndrome associated with the development of nervous system tumors, including vestibular schwannomas (VS), meningiomas, and ependymomas. Although considered a rare illness, it is a source of significant morbidity, mainly due to early hearing loss leading to decreased autonomy and productivity among young adults. Bevacizumab, a monoclonal antibody against VEGF, has been shown to improve audition and tumor size in observational studies on NF2-associated VS. The most common limitations in the literature include the lack of reliable control groups, the paucity of data on quality of life, and the lack of detailed audiology testing guidelines. Moreover, the cost of bevacizumab is a limiting factor in access to care. In our Canadian tertiary care center, bevacizumab has been offered to NF2 patients with VS complications without specific indications on optimal treatment initiation time or duration. We present a hybrid cohort study protocol with retrospective and prospective arms aimed at measuring the impacts of introducing a standardized treatment and surveillance protocol on tumor growth, hearing outcomes, and quality of life. Patients from the multidisciplinary neurofibromatosis clinic at the University of Montreal Health Center, Canada, will be evaluated for inclusion in the prospective arm through regular audiological evaluations and imaging. Eligible individuals will receive bevacizumab at an initial dose of 5 mg/kg every 2 weeks for a year while participating in serial audiological, radiological, and quality of life assessments. The results will be compared to those of our historical cohort. Our primary outcomes will be tumor growth rate (% per year) for vestibular schwannomas, meningiomas and ependymomas, audiological test results, and quality of life and subjective hearing estimated through standardized questionnaires (SF-36, SSQ). We hypothesize that patients enrolled in the prospective arm will show improved clinical response compared to our historical cohort.